JAGN1 Deficient Severe Congenital Neutropenia: Two Cases from the Same Family - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2015)
Recently autosomal recessively inherited mutations in the gene encoding Jagunal homolog 1 (JAGN1) was described as a novel disease-causing gene of severe congenital neutropenia (SCN) JAGN1-mutant neutrophils were characterized by abnormality in endoplasmic reticulum structure, absence of granules, abnormal N-glycosylation of proteins and susceptibility to apoptosis. These findings imply the role of JAGN1 in neutrophil survival. Here, we report two siblings with a homozygous mutation in JAGN1 gene, exhibiting multisystemic involvement.
Keywords: Clinical features; severe congenital neutropenia; JAGN1; MUTATIONS; ELA2